The Use of Instructional Videos in Enhancing Arabic Language Comprehension: A Qualitative Study and Systematic Literature Review - Jihan Gina Fadila; Ahmad Nur Mizan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study integrates descriptive qualitative research and systematic literature review approaches to analyze the use of instructional videos in enhancing Arabic language comprehension. The qualitative study involved 12 fourth-semester students from the Arabic Language Education Program at UIN Raden Intan Lampung over a 12-week period, employing participatory observation, in-depth interviews, and document analysis for data collection. Meanwhile, the systematic literature review analyzed five empirical studies on the effectiveness of video media in Arabic language learning published from 2020-2024. Results demonstrate that instructional video use significantly improves students' Arabic language comprehension across three dimensions: (1) vocabulary and listening skills (istima'), (2) contextual-cultural understanding, and (3) learning motivation and self-regulated learning. These improvements occur through mechanisms of cognitive load reduction, provision of comprehensible input, and increased intrinsic motivation. Findings reveal three key factors influencing video effectiveness: (a) instructional design quality (duration, narration speed, open captioning, and interactive elements), (b) pedagogical support strategies by instructors, and (c) technological infrastructure readiness. Students with lower initial proficiency benefit most from video learning, though they encounter certain technical and linguistic barriers. This study recommends integrating video as a core learning component, developing videos based on specific needs, and providing digital literacy training for educators.